3D Compton scattering imaging with multiple scattering: analysis by FIO and contour reconstruction. (4th May 2021) - Rigaud, Gaël
Abstract: 3D Compton scattering imaging (CSI) is an upcoming concept exploiting the scattering of photons induced by the electronic structure of the object under study. The so-called Compton scattering rules the collision of particles with electrons and describes their energy loss after scattering. Although physically relevant, multiple-order scattering was so far not considered and therefore, only first-order scattering is generally assumed in the literature. The purpose of this work is to argument why and how a contour reconstruction of the electron density map from scattered measurement composed of first- and second-order scattering is possible (scattering of higher orders are here neglected). After the development of integral representations for the first- and second-order scattering, we approximate these models by Fourier integral operators (FIO) and study their smoothness properties. The second-order scattered radiation reveals itself to be structurally smoother than the radiation of first-order indicating that the contours of the electron density are essentially encoded within the first-order part. This opens the way to contour-based reconstruction techniques when considering multiple scattered data. Our main results, modeling and reconstruction scheme, are successfully implemented on synthetic and Monte-Carlo data.